Empirical Research of Development Features of the Organizational Culture of Construction Enterprises - Rynkevich, N. (Економічний вісник Донбасу, 2019)
Currently, the problems of developing the organizational culture of enterprises of various types of economic activity are being updated taking into account their specifics. This allows you to achieve greater flexibility and the ability to quickly respond to changes in the internal and external environment, to strengthen competitive positions in the sales markets, which corresponds to modern business conditions. The purpose of this study is an empirical research of the organizational culture of construction enterprises, identifying trends in its development in modern conditions and improving the methodological approach to assessing the level of development. As a result of the research, the dynamics of the number of employed and hired workers in the construction industry is analyzed. The results of an expert survey are presented to identify current problems, barriers, features, trends and ways of developing the organizational culture of construction enterprises in Ukraine. An assessment of the level of development of the organizational culture of enterprises. An integrated methodology for assessing the organizational culture of construction enterprises is proposed. Testing of this methodology showed that the surveyed enterprises have an average level of organizational culture development (0.69), since the value of the integral indicator is in the range of 0.5-0.75. На даний час актуалізуються проблеми розвитку організаційної культури підприємств різних видів економічної діяльності з урахуванням їх специфіки. Це дозволяє досягти більшої гнучкості й здатності оперативно реагувати на зміни внутрішнього і зовнішнього середовища, посилити конкурентні позиції на ринках збуту, що відповідає сучасним умовам господарювання. Мета даного дослідження полягає в емпіричному дослідженні особливостей організаційної культури будівельних підприємств, виявленні тенденцій її розвитку в сучасних умовах та удосконаленні методичного підходу до оцінювання рівня розвитку. У результаті дослідження проаналізовано динаміку кількості зайнятих і найманих працівників у сфері будівництва. Викладено результати проведеного експертного опитування з метою виявлення сучасних проблем, бар’єрів, особливостей, тенденцій та шляхів розвитку організаційної культури будівельних підприємств в Україні. Виконано оцінку рівня розвитку організаційної культури підприємств. Запропоновано інтегральну методику оцінки організаційної культури будівельних підприємств. Апробація даної методики показала, що обстежені підприємства мають середній рівень розвитку організаційної культури (0,69), оскільки значення інтегрального показника знаходиться в межах 0,5–0,75. В настоящее время актуализируются проблемы развития организационной культуры предприятий различных видов экономической деятельности с учетом их специфики. Это позволяет достичь большей гибкости и способности оперативно реагировать на изменения внутренней и внешней среды, усилить конкурентные позиции на рынках сбыта, что соответствует современным условиям хозяйствования. Цель данного исследования заключается в эмпирическом исследовании особенностей организационной культуры строительных предприятий, выявлении тенденций ее развития в современных условиях и совершенствовании методического подхода к оценке уровня развития. В результате исследования проанализирована динамика количества занятых и наемных работников в сфере строительства. Изложены результаты проведенного экспертного опроса с целью выявления современных проблем, барьеров, особенностей, тенденций и путей развития организационной культуры строительных предприятий в Украине. Выполнена оценка уровня развития организационной культуры предприятий. Предложена интегральная методика оценки организационной культуры строительных предприятий. Апробация данной методики показала, что обследованные предприятия имеют средний уровень развития организационной культуры (0,69), поскольку значение интегрального показателя находится в пределах 0,5-0,75.